Report
1941-11 038-0024-011 13 into the Basque Children's Committee, and Miss Garrett, who was its able Secretary, has now gone over to the International Commission. The National Joint Committee feels convinced that the boys will, if anything, gain by the change — particularly as Dr. Collier, Dr. Russell, Miss Pye and other members of the International Commission have been so closely associated with the work from the beginning, and are members of the National Joint Committee. In co-operation with the Trade Union movement the Basque Boys' Training Committee found good openings for all the boys in engineering, agricultural, tailoring and other industries. Many of them through attending evening schools are able to combine their practical work with a sound theoretical training. One clever boy worked for a year and passed his matriculation — the first of the Basque boys to achieve this distinction. The opportunity is now being made for him to attend one of the provincial universities. One patron has become so attached to two of the boys that he is paying £200 a year for their education. Another boy is on a Training Ship, training for the merchant service. The boys are nearly all children of factory workers or peasants and the policy has been to place them in good working-class homes in the district in which they work. This was done also to help them to improve their knowledge of English and to adapt themselves more easily to the conditions of English life. At the same time, in an effort to preserve their Spanish culture, a monthly magazine was started, edited by the boys themselves, a lending library for Spanish books was got together and discussions and lectures organised in Spanish and a Youth Group was formed. The Home Office viewed the efforts to procure employment for the boys quite sympathetically, for some time, before the outbreak of war; provided the conditions of their work were similar to those of British workers. Few of the boys are yet wholly self-supporting as many are learning trades which require apprenticeship. In some cases small fees must be paid; in others maintenance must be found. In the case of the younger children individually adopted, war conditions are constantly forcing their foster parents to return them to the Committee's care and fresh homes have to be found at short notice, or further financial assistance sent. There is also a further responsibility for the Senoritas, young teachers, who came over with the children, few of whom have been able to return to Spain. 292/946/38/24(XI)